Eh-Sayyeh, Jordanien: Die Arbeiten des Jahres 2013 - Bartl, Karin; Kafafi, Zeidan (e-Forschungsberichte des DAI, 2023)
The site of eh-Sayyeh is one of the few previously known settlements of the Neolithic period in northern Jordan. Former research in the 1990s revealed a settlement sequence of the 8th to the 6th Millennium BC. The assemblage of Early and Late Neolithic layers allows investigations into the transition between these periods and the earliest appearance of pottery. The main objective of the project is a detailed stratigraphic-chronological analysis of selected settlement areas and the comparison of these results with developments in the northern Levant.